Efficacy Study of Carrageenan as an Alternative Infused Material (Filler) in Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) Porous 3D Scaffold - Nor Syamimi Che Johari; Syazwan Aizad; Saiful Irwan Zubairi (International Journal of Polymer Science)
Polymeric porous 3D scaffold plays an important role in culturing mammalian cells as ex vivo model. However, the scaffold used is ineffective due to its structural and cell acceptability weaknesses. Therefore, this research attempts to overcome the weaknesses by using carrageenan from red seaweed Kappaphycus alvarezii as an alternative infused material (filler) of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) porous 3D scaffold. The 3D scaffold was conventionally fabricated using the solvent-casting particulate-leaching (SCPL) method. Carrageenan was later infused into 3D porous scaffolds under vacuum pressure and freeze-drying process. Five carrageenan concentrations were prepared and its physicochemical properties such as pH and viscosity were carried out on each concentration to determine the best solutions to produce a new composite 3D structure. The preliminary result shows that carrageenan concentrations of 2, 4, and 6% (w/v) were considered the best solutions for the infusion process due to its stable rheology properties. The pH and viscosity profiles of three selected carrageenan solutions were exhibited in the range of 9.00–9.20 and 0.047–1.144 Pa·s, respectively. Moreover, the incorporated carrageenan gel fraction was in the range of 4.30% to 14.95% (w/w) which was determined by gravimetric analysis and dye staining method (visual assessment). The well-infused carrageenan 3D scaffold was further characterized based on its internal morphology and degradability study. The vertical cross-sections of the scaffolds revealed homogeneous accumulation of dried gelatinous carrageenan which was covered throughout its pores wall. The degradation rate (K) of the carrageenan infused 3D scaffold was between 0.01±1.66 (mg/day) and 0.03±3.23 (mg/day). The higher the carrageenan concentration used, the faster the degradation rate occurring (p<0.05). The 3D infused scaffold of 4% (w/v) carrageenan concentration (S2) produced a moderate degradation rate of 0.02±1.55 (mg/day) with a sustained structural integrity up to 28 days. The carrageenan infused scaffold of 4% (w/v) was demonstrated to be the best 3D structure for a long-term cell culture (>2 weeks). In conclusion, the usage of carrageenan as a composite material exhibits its great potential to be used in tissue engineering application and 3D cell culture model.